Rhetorics of evidence: science - media - culture - Kramer, Olaf; Pelzer, Michael (Visual rhetoric, 2024)
"Sixteen essays examine the use of evidence in culture, media, and science communication, ranging from paleontology, meteorology, neurological science/computation to literature, film, photography, and civic rhetoric. In full color"--